Pengaruh Judi Online Terhadap Peningkatan Kriminalitas Digital: Kajian Normatif Hukum Pidana Berdasarkan KUHP di Indonesia - Tiara Hazizah; Hana Faridah (CV WAHANA PUBLIKASI, 2026)
The rapid development of digital technology has brought a double impact on Indonesian society. On one hand, it facilitates access to information, yet on the other, it opens avenues for the proliferation of online gambling, which correlates with various digital crimes. This study aims to normatively examine how criminal law provisions in the Penal Code and related regulations respond to the phenomenon of online gambling and its implications for the escalation of digital crime in Indonesia. Using a normative juridical method with statutory and conceptual approaches, this study examines primary and secondary legal materials collected through library research and analyzed qualitatively to evaluate the adequacy of Indonesia’s legal framework in addressing online gambling-related crimes. This study finds that online gambling is not merely a standalone criminal act but also drives derivative crimes such as data theft, fraud, and money laundering. The existing legal framework, particularly Article 303 of the Penal Code in conjunction with the ITE Law, has not fully addressed the complexity of digital crimes based on online gambling. Systematic legal reform and consistent enforcement are urgent needs.